Halide perovskite memtransistor enabled by ion migration. (31st July 2020) - Haque, Farjana; Mativenga, Mallory
Abstract: We exploit the problem of ion migration in the halide perovskite CH3 NH3 PbI3 (MAPbI3 ) by developing a memtransistor (i.e. hybrid memristor and transistor) with the field-effect transistor geometry. Application of an electric field between the drain and the source results in resistive switching from a high resistance state (HRS) to a low resistance state (LRS) due to dynamic redistribution of ions in the MAPbI3 layer. The gate enables continuous tuning of this LRS across several orders of magnitude. The LRS persists after removing the power supply and the memtransistor can be switched back to the HRS by reversing the bias polarity. Excellent state retention is demonstrated for 10 4  s and a switching ratio (HRS/LRS) of 10 2 is maintained for 1000 cycles, thus confirming good retention and cyclic endurance for the resistive switching behavior. Continuous tuning of the state conductance is essential for neuromorphic architectures and hard to achieve with two-terminal memristors.